Penciptaan Keramik Earthenware Dan Stoneware Pada Bedroom Di Hotel Fourteen Roses Boutique, Legian, Kuta, Badung - Suartana, Putu Erik; Artayani, Ida Ayu Gede; Laba, I Nyoman (Pusat Penerbitan LPPM ISI Bali, 2024)
A hotel is an accommodation facility that provides lodging facilities as well as commercial food and beverage services. Because it is commercial, the hotel is equipped with supporting facilities such as; halls, lobby, restaurants, management offices and others. Hotels are divided into several types whose classification is reviewed from various purposes such as; the purpose of the guest's arrival, the length of the guest's stay, the number of rooms, the location and based on the division of star hotel clusters. The number of hotels spread across Bali is directly proportional to the increasing need for exterior and interior complementary products, it is interesting to explore further in creating ceramic products made of earthenware and stoneware as an answer to the exterior and interior needs of a hotel. Based on this phenomenon, then this was realized in the implementation of the MBKM program of the Independent Project scheme. SP Gustami creation method is used such as exploration, design, and embodiment in the process of realizing the creation of ceramic products. Exploration is carried out in two steps, namely idea exploration and physical exploration as the basis for designing ceramic products. The design is carried out by visualizing the idea in the form of alternative sketches and selected sketches. The final process of this method is that the embodiment is carried out according to the selected sketch. The result is in the form of 4 functional ceramic products in the form of teapot products, shampoo holders, snack and fruit holders, and sleeping lamps, as well as 1 wall decoration work, by applying a brick motif arrangement decoration inspired by the Fourteen Roses Boutique Hotel concept, and applying glaze colors inspired by pink and maroon rose colors. The products that have been produced will later be used in the Intermediate Room of the Fourteen Roses Boutique Hotel aiming to provide comfort and harmony for each user.